Resiliensi Perempuan Pasca Kematian Pasangan Hidup pada Jemaat Christ Oikos Church - Junkhian Junkhian; Iskak Sugiyarto; Daryanto Daryanto (Anugerah : Jurnal Pendidikan Kristiani dan Kateketik Katolik, 2024)
For a woman, losing a spouse is a process in life that must be dealt with in order to go on. Resilience is the ability and capacity of each individual to deal with adversity. The purpose of this study is to better understand how women develop resilience in the face of obstacles and life stages, as well as the variables that affect women's resilience in the wake of a spouse's death. Serving as an accompaniment serves as a gateway for the church to assist members who are going through a difficult time of mourning. In this qualitative study, three female respondents were interviewed at Christ Oikos Church using a phenomenological technique. The study's findings demonstrate the three female respondents' extraordinary resilience in that they are able to get back up and carry on with their lives. Keywords: Resilience; Women; Grief